Sted, trivsel og skoleavbrudd - individuelle og strukturelle mekanismer i skolen synliggjort gjennom ungdoms fortellinger: En studie med Henri Lefebvres triademodell som analytisk prisme - Halvorsen, Torill Aagot; Bunting, Mette (Nordic Journal of Comparative and International Education (NJCIE), 2019)
The aim of this article is to examine young people’s narratives about place in the dropout process and how they make sense of everyday practices in social places. Studying young people’s experiences about place can provide insight of how change and continuity can influence decisions and practices. This article is based on preliminary findings from the longitudinal ethnographic study [Name of project] in which 71 youths from the county of Telemark are regularly interviewed. The article presents excerpts from the stories, which give us insight into everyday practices, relationships and experiences from school activities. The French professor, philosopher and sociologist Henri Lefebvre, known to city planners and architects, was also engaged in education and teaching. However, in the Nordic countries, his work has largely been ignored by the pedagogical and educational science. In this article, we want to highlight his critical thinking on education where he introduces pedagogical concepts, principles and mind-sets that might have a significant importance when analyzing the young people’s narratives, trying to understand their everyday practice. The results in this study indicate that young people struggle in different ways with their everyday school practice, social space and the place they grow up, which again influence their endeavors in completing their education. Hence, it is imperative for educators to comprehend the influence the extended meaning of place, space and relationships have on young people’s opportunities to succeed in completing school.